Embedding ESG practices into corporate strategy: a pathway to brand loyalty through consumer brand identification in the cosmetics industry - Norsyarmimi Binti Che Lah; Karpal Singh Dara Singh; Sajead Mowafaq Alshdaifat; Jalal Rajeh Hanaysha (Discover Sustainability)
Abstract This study examines the effects of environmental, social and governance (ESG) practices on consumer brand identification and brand loyalty in the cosmetics industry. A structured questionnaire was developed based on validated scales from past studies after which the data was collected from female customers of cosmetic brands in Malaysia. In total, 307 valid responses were obtained from the respondents and analysed via the Partial Least Squares Structural Equation Modelling (PLS-SEM). The analysis revealed that environmental and governance practices were important predictors of consumer brand identification and positively affected brand loyalty. Furthermore, brand identification was found to mediate the effect of environmental and governance practices on brand loyalty. In contrast, the effect of social practices on brand identification was found to be insignificant and no mediating effect of brand identification was observed between social practices and brand loyalty. This study makes significant contributions to practice by making a strong business case for ESG to be adopted as a legitimate corporate strategy in fostering band identification and brand loyalty. The study also enriches the literature on ESG practices, brand identification and loyalty with new insights from the cosmetics industry in Malaysia; an area that has not received much scholarly attention till date.